CRITICAL DISCOURSE ANALYSIS OF NEOLIBERAL IDEOLOGY IN TIMOTHY RONALD'S 'FIN-FLUENCER' CONTENT - Perdana, Candra Halim; Nabelia, Fitria Rizka (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This study critiques the reproduction of neoliberal ideology within Timothy Ronald’s financial content on YouTube using Norman Fairclough’s Critical Discourse Analysis (CDA). By examining three dimensions-text, discourse practice, and social practice-the analysis of his most popular videos reveals the use of mechanistic metaphors, casual linguistic styles, and personal success narratives to establish authority. The findings show that such content effectively constructs neoliberal subjects (homo economicus) by emphasizing absolute individual responsibility, reducing poverty to a moral failing, and disregarding structural factors. Ultimately, this discourse reinforces the dominance of market logic over all aspects of individual life in the digital era.